2023
DOI: 10.48550/arxiv.2301.05500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RCPS: Rectified Contrastive Pseudo Supervision for Semi-Supervised Medical Image Segmentation

Abstract: Medical image segmentation methods are generally designed as fully-supervised to guarantee model performance, which require a significant amount of expert annotated samples that are high-cost and laborious. Semi-supervised image segmentation can alleviate the problem by utilizing a large number of unlabeled images along with limited labeled images. However, learning a robust representation from numerous unlabeled images remains challenging due to potential noise in pseudo labels and insufficient class separabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the field of medical image segmentation, Zhao et al proposed a pseudo supervision method based on consistency regularization and uncertainty evaluation [29], which reduced the influence of the potential noise of pseudo-labels on segmentation results in semi-supervised learning. Dong et al [30] proposed an unsupervised domain adaptive framework based on an antagonistic network, and applied it to semi-supervised learning on the JSRT (Japanese Society of Radiological Technology) datasets.…”
Section: Semi-supervised Learning In Medical Image Analysismentioning
confidence: 99%
“…In the field of medical image segmentation, Zhao et al proposed a pseudo supervision method based on consistency regularization and uncertainty evaluation [29], which reduced the influence of the potential noise of pseudo-labels on segmentation results in semi-supervised learning. Dong et al [30] proposed an unsupervised domain adaptive framework based on an antagonistic network, and applied it to semi-supervised learning on the JSRT (Japanese Society of Radiological Technology) datasets.…”
Section: Semi-supervised Learning In Medical Image Analysismentioning
confidence: 99%
“…Semi-/self-supervised methods have been shown to work well on generic noisy data and limited labels with uncertainties (Dinsdale et al, 2022;Chen et al, 2020;Feyjie et al, 2020;Perone et al, 2019;Sundaresan et al, 2022;Fischer et al, 2023;Du et al, 2023). In particular, contrastive learning, which aims to learn image features that are similar or different between segmentation classes (Chen et al, 2020;Zhao et al, 2023), has been used to segment histopathological images (Wu et al, 2022;Lai et al, 2021). Similarly, perturbationbased self-ensembling and temporal ensembling, where average predictions from prior epochs are used as pseudo-labels for training the current epoch (Li et al, 2020;Perone et al, 2019), have been shown to perform well in segmentation tasks with minimal manual annotations for training.…”
Section: Introductionmentioning
confidence: 99%